2020
DOI: 10.1002/ppul.25207
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of oral glucose tolerance testing in cystic fibrosis

Abstract: Introduction Annual oral glucose tolerance testing (OGTT) is the recommended screening modality for cystic fibrosis‐related diabetes (CFRD) in patients with cystic fibrosis (CF). This study aimed to determine if there were patterns of progression of worsening glucose homeostasis in pediatric CF patients and to explore any relationship to lung function. Methods We conducted a retrospective cohort study of CF patients, ages 10–18 years, without CFRD and with ≥3 OGTT from 2013 to 2016. Latent class mixture models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
0
0
1
Order By: Relevance
“…The onset of CFRD is accompanied by an exacerbation of the deterioration of the nutritional status and pulmonary functions attributed to insulin deficiency and recurrent lung disease exacerbations, resulting in an increased number of hospitalizations, a higher prevalence of infections from P. aeruginosa and Burkholderia cepacia, and diminished overall physical health. Moreover, several studies have demonstrated that clinical deteriorations can initiate up to 4-5 years before a formal diagnosis of diabetes is made, as indicated by Patel et al in 2021 [58]. CFRD is associated with reduced life expectancy and elevated mortality and morbidity rates, with no observable gender-based disparities in mortality, according to the findings of Ballmann (2021) and Suppakitjanusant et al (2023) [6,59].…”
Section: Complications Developmentmentioning
confidence: 98%
“…The onset of CFRD is accompanied by an exacerbation of the deterioration of the nutritional status and pulmonary functions attributed to insulin deficiency and recurrent lung disease exacerbations, resulting in an increased number of hospitalizations, a higher prevalence of infections from P. aeruginosa and Burkholderia cepacia, and diminished overall physical health. Moreover, several studies have demonstrated that clinical deteriorations can initiate up to 4-5 years before a formal diagnosis of diabetes is made, as indicated by Patel et al in 2021 [58]. CFRD is associated with reduced life expectancy and elevated mortality and morbidity rates, with no observable gender-based disparities in mortality, according to the findings of Ballmann (2021) and Suppakitjanusant et al (2023) [6,59].…”
Section: Complications Developmentmentioning
confidence: 98%
“…Традиционно принято считать, что снижение нутритивного статуса (НС) и ухудшение функции легких приводят к МЗСД, что является причиной ранней смертности и ухудшает качество жизни пациентов [4][5][6][7]. До 30 лет доживают менее 25% пациентов с МЗСД по сравнению с 60% пациентов с МВ без НУО [8,9]. С возрастом распространенность МЗСД возрастает: у 2-5% детей до 10 лет, у 20% подростков и 40-50% взрослых с МВ развивается МЗСД [10][11][12][13].…”
Section: Introductionunclassified